Eating disorders among university students: a public health challenge. An European study. (13th November 2019) - Ladner, J; Lukács, A; Brumboiu, I; Ciobanu, E; Croitoru, C; Sasvári, P; Tavolacci, M P
Abstract: Background: Eating disorders (ED) and behavioural risk factors among students in higher education remain to be investigated. The aim of the study was to identify the prevalence of ED and the behavioural factors associated with ED in university students in four European universities: Chisinau (Ch) in Republic of Moldava, Cluj-Napoca (CN) in Romania, Miskolc (Ms) in Hungary and Rouen (R) in France. Methods: In the four countries, students in higher education completed an anonymous standardized self-questionnaire, from 2016 to 2018. The questionnaire collected age, gender (M, W), housing, curricula, smoking, cannabis consumption, alcohol abuse problems (ADOSPA test), and perceived stress (Cohen score). The Sick, Control, One stone, Fat, Food (SCOFF scale) screening test was used to identify student with ED. Results: A total of 3076 students were included, 705 in Ch, 582 in CL, 534 in Ms and 1255 in R. The sex-ratio was M:F=0.31 Ch, 0.30 in CN, 0.44 in Ms and 0.66 in R. The mean age was 21.2 (SD = 3.98) in Ch, 21.2 (SD = 3.2) in CL, 23.8 (SD = 5.1) in Ms and 20.0 (SD = 3.4) in R. The global prevalence of ED was 23.8%. According to the gender, the prevalence of ED in the four universities was 14.7% in M and 38.3% in W in Ch, 21.8% in M and 24.7% in W in CN, 19.7% in M and 21.4% in W in Ms and 16.1% in M and 34.0% in W in R (p < 10-4). After logistic regression, significant positive relation between the positive SCOFF was observed with female gender, alcohol abuse problems and stress level. Conclusions: ED prevalence patterns were quite similar in the four countries, with high prevalence of ED, even in men. Associated behavioural risk-factors were quite similar. It might be necessary in the future to screen students for potential ED upon entry to the university and also to inform student about the risk of ED and advise them to consult a healthcare professional. Key messages: Our study highlights the high prevalence of eating disorders, with similar behaviours in university students in four countries. Because of the detrimental effects of ED on physical and emotional health, it seems mandatory to set up public health programs (health promotion, prevention).